A feasibility study of the costs and consequences of improving the oral health of older people in care homes: findings from the TOPIC study - Ciaran O’Neill; Paul R. Brocklehurst; Saif Syed; Michelle Harvey; Sana Daniyal; Sinead Watson; Nia Goulden; Anna Verey; Peter Cairns; Anja Heilmann; Zoe Hoare; Frank Kee; et al. (BMC Oral Health)
Abstract Background In the UK older adults in care homes have exhibited poorer oral health than age-equivalent persons in the community. In response the National Institute for Health and Care Excellence issued guidance (NG48) on the maintenance and improvement of oral health in this group. Currently, there is little evidence on the cost-effectiveness of such interventions. The aim of this study was to examine the feasibility of evaluating an intervention framed around NICE guidance. Methods The study was undertaken in 22 care homes across 2 sites with eligibility criteria used to ensure access to residents for whom the oral health care intervention was relevant and who could consent to participation. The intervention followed the guidance issued by NICE in respect of care staff knowledge; oral health assessment and development of care plans, and provision of daily mouth care to residents. Quantitative and qualitative data were collected from residents and care home managers and interviews undertaken with a range of stakeholders. Quantitative data from residents comprised EQ5D5L at baseline, 6 and 12 months, qualitiative data was taken from interviews. Descriptive statistics and a discussion of themes raised in surveys and interviews was undertaken. The trial was registered with the UK’s Clinical Study Registry (ISRCTN10276613) on 17/04/2020. Results Of 119 residents recruited, 115 provided usable EQ5D5L data at baseline. The data had good face validity. Managers from 7 of 22 homes provided responses to the care home survey. All responding care homes routinely recorded information on care provided to residents and 5 of the 7 recorded information on the funding source for that care. Care assistant time was a key consideration among managers in terms of resource use. Residents overall quality of life was a key consideration among managers in terms of outcomes. Among key stakeholders, there was a universal appreciation of the need to improve the evidence base on the value for money of interventions framed around NG48. Conclusion The study supports the case for the conduct of an economic evaluation in a definitive trial to address a manifest gap in the evidence base on oral hygiene interventions in this context.